Clinical Utility of a Hand-Held Scanner for Breast Cancer Early Detection and Patient Triage - Julie M. Clanahan; Sanjana Reddy; Robyn B. Broach; Anne F. Rositch; Benjamin O. Anderson; E. Paul Wileyto; Brian S. Englander; Ari D. Brooks (JCO Global Oncology, 2020)
PURPOSE Globally, breast cancer represents the most common cause of cancer death among women. Early cancer diagnosis is difficult in low- and middle-income countries, most of which are unable to support population-based mammographic screening. Triage on the basis of clinical breast examination (CBE) alone can be difficult to implement. In contrast, piezo-electric palpation (intelligent Breast Exam [iBE]) may improve triage because it is portable, low cost, has a short learning curve, and provides electronic documentation for additional diagnostic workup. We compared iBE and CBE performance in a screening patient cohort from a Western mammography center. METHODS Women presenting for screening or diagnostic workup were enrolled and underwent iBE then CBE, followed by mammography. Mammography was classified as negative (BI-RADS 1 or 2) or positive (BI-RADS 3, 4, or 5). Measures of accuracy and κ score were calculated. RESULTS Between April 2015 and May 2017, 516 women were enrolled. Of these patients, 486 completed iBE, CBE, and mammography. There were 101 positive iBE results, 66 positive CBE results, and 35 positive mammograms. iBE and CBE demonstrated moderate agreement on categorization (κ = 0.53), but minimal agreement with mammography (κ = 0.08). iBE had a specificity of 80.3% and a negative predictive value of 94%. In this cohort, only five of 486 patients had a malignancy; iBE and CBE identified three of these five. The two cancers missed by both modalities were small—a 3-mm retro-areolar and a 1-cm axillary tail. CONCLUSION iBE performs comparably to CBE as a triage tool. Only minimal cancers detected through mammographic screening were missed on iBE. Ultimately, our data suggest that iBE and CBE can synergize as triage tools to significantly reduce the numbers of patients who need additional diagnostic imaging in resource-limited areas.